Multifaceted structures of mathematics education in the Philippines: a case analysis - Luzano, Jay Fie (2024)
Mathematics education, as a cornerstone of academic curricula globally, varies widely across regions due to diverse cultural, economic, and educational influences. This study considered the Philippines' unique socio-cultural and economic landscape and its localized multifaceted educational structures. This research employed a qualitative case study method in exploring the lived experiences of mathematics educators in the Philippines on the multifaceted structures of mathematics education that influence and shape their professional practices. Findings reported eight (8) emerging themes on the multifaceted structures of mathematics education in the Philippines, namely: (1) Professional Development and Training Needs; (2) Curriculum and Instructional Challenges; (3) Resource Constraints; (4) Support and Collaboration among Educators; (5) Assessment and Evaluation Practices; (6) Student Engagement and Motivation; (7) Influence of Socioeconomic Factors; and (8) Educational Policies and Systemic Issues. Addressing the multifaceted challenges in the Philippines' mathematics education system requires a holistic approach that empowers teachers, enhances instructional quality, and improves educational outcomes through robust training, relevant curricula, equitable resources, collaborative environments, and inclusive policy-making to support and benefit both teachers and students.